T cell activation Rho GTPase activating protein (TAGAP) is upregulated in clinical and experimental arthritis. (April 2018) - Arshad, Maria; Bhatti, Attya; John, Peter; Jalil, Fazal; Borghese, Federica; Kawalkowska, Joanna Z.; Williams, Richard O.; Clanchy, Felix I.L.
Abstract: Genome-wide association studies have identified various susceptibility variants and loci associated with incidence of rheumatoid arthritis (RA) in different populations. One of these is T cell activation Rho GTPase activating protein ( TAGAP ). The present study sought to measure the expression of TAGAP in RA patients, CD4 + T cells subsets from healthy humans and in mice with collagen-induced arthritis. Peripheral blood mononuclear cells (PBMC) from RA patients and tissues of arthritic mice at different stages of the disease were used for the evaluation of TAGAP mRNA expression. Increased TAGAP expression was observed in RA patients compared to healthy controls, and there were differences in the expression level of TAGAP in the tissues of mice with experimental arthritis. Gene expression in CD4 + T cells from healthy humans was greatest 4 h after activation and protein expression was greatest after 24 h. The expression of TAGAP was not correlated with CD4 + lymphocyte subsets which were enriched for functionally defined subsets (Th17, Treg, Th1), further indicating its utility as an indicator of lymphocyte activation. These findings indicate that increased TAGAP expression is a distinguishing feature of inflammatory disease and further highlight the role of TAGAP in RA susceptibility.